PERSEPSI WISATAWAN TERHADAP PELEBON PURI UBUD KECAMATAN UBUD, KABUPATEN GIANYAR - Pande Agus, Pande Putu Agus Putrabawa; I Putu Suyasa Ariputra; Wiyasa, I Putu Wiyasa (UHN IGB Sugriwa Denpasar, 2025)
The Pelebon Ceremony At Puri Ubud, Gianyar, Bali Is A Hindu Balinese Funeral Ritual Imbued With Deep Spiritual Significance, While Also Serving As A Major Cultural Tourism Attraction. However, another potential issue may arise, as Merton also reminds us of the risk of dysfunction, for instance when tourists perceive the ceremony merely as entertainment or a commodity, thereby neglecting its sacred dimension. This Study Aims To Analyze The Perceptions Of Balinese Domestic Tourists, Non-Balinese Domestic Tourists, And International Tourists Toward The Pelebon Ritual, Employing Robert K. Merton’s Structural Functional Theory As The Analytical Framework. A Qualitative Descriptive Method Was Applied Through In-Depth Interviews, Direct Observations, And Literature Reviews. The Findings Reveal That Balinese Domestic Tourists Emphasize The Sacred Function Of Pelebon As A Religious Obligation, Ancestral Heritage Preservation, And Communal Identity Reinforcement. Non-Balinese Domestic Tourists Perceive Pelebon As An Intercultural Experience That Enhances Multicultural Awareness And Strengthens National Identity, Though It Is Sometimes Interpreted Merely As An Exotic Spectacle. Meanwhile, International Tourists Appreciate Pelebon As A Unique Aesthetic And Spiritual Experience That Elevates Bali’s Global Image, Yet It Also Carries The Risk Of Cultural Commodification.